Desenvolvimento e aplicação do Elisa indireto com a nucleoproteína recombinante (NPR) do vírus da doença de Newcastle - Silva, Ketherson Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Newcastle disease virus (NDV) causes one of the most important infectious diseases for chickens, due to the high negative impacts for health and the demands of trade barriers to poultry industry. This requires the constant development of increasingly more effective diagnostic techniques. In this context, the nucleoprotein (NP) of VDN is one of the ideal antigenic components for immunodiagnostics, because it is more conserved and has a high immunogenicity, so that NP may improve the performance of serodiagnosis of NDV. Thus, this study aimed to determine the production profiles of anti-NDV antibodies of IgA, IgM and IgG isotypes, using recombinant NP (rNP) of VDN as a target antigen. Serum and tear samples were collected from commercial poultry flocks, and from SPF birds experimentally infected with the LaSota vaccine strain of NDV. The indirect ELISA method using the NPr VDN as coating antigen was standardized and used for the detection of anti-NDV chicken antibody isotypes IgG, IgM in serum samples and antibodies of both isotypes added of IgA isotype for lacrimal secretion samples. This ELISA method with NPr was effectively able to differentiate NDV-positive and NDV-negative serum and tear samples, and in the birds subjected to a experimental infection with vaccine strain, the seroconversion was detected earlier for the antibodies of the IgA (tear) and IgM (tear and serum) isotypes, which have reached maximum concentration on the 7th day post-infection (pi), while the IgG anti-NDV antibody levels began to be detected later and peaked at 14 days pi. Moreover, the application of ELISA in serum and lachrymal samples collected from commercial layer chickens,with the detection of two (IgG and IgM for serum samples) or three isotypes (IgG, IgM and IgA for lachrymal samples) of anti-NDV antibodies, resulted in the highest detection frequencies than each antibody isotype was individually detected. By comparing the results of serum samples for ...

O vírus da doença de Newcastle (VDN) provoca uma das doenças infecciosas mais importantes para as aves domésticas, devido aos elevados impactos negativos para a saúde aviária e a interposição de barreiras comerciais para a indústria avícola. Isso requer a constante evolução de técnicas cada vez mais eficazes de diagnóstico para esse vírus. Neste contexto, a nucleoproteína (NP) de VDN é um dos componentes antigênicos ideais para uso no imunodiagnóstico, porque é mais conservada e tem uma elevada imunogenicidade, de modo que NP pode melhorar o desempenho de sorodiagnóstico do VDN. Assim, este estudo teve como objetivo determinar os perfis de produção de anticorpos (Acs) anti-VDN dos isótipos IgA, IgM e IgG, usando NP recombinante (NPr) do VDN como um antígeno alvo. Amostras de soro e de lágrima foram colhidas de plantéis comerciais de aves de postura e também de aves SPF infectadas experimentalmente com a estirpe vacinal LaSota do VDN. O método de ELISA indireto, usando a NPr do VDN como antígeno de revestimento, foi padronizado e utilizado de forma bem sucedida para a detecção de Acs de galinha anti-VDN dos isótipos IgG e IgM em amostras de soro, e de ambos os isotipos mais IgA para amostras de secreção lacrimal. Ainda, este método de ELISA com NPr foi capaz de diferenciar amostras positivas das negativas para o VDN de soro e de lágrima, e nas aves submetidas à infecção experimental com a estirpe vacinal LaSota, a soroconversão foi detectada mais precocemente para os anticorpos do isótipo IgA (lágrima) e IgM (lágrima e soro), que alcançaram uma concentração máxima no sétimo dia após a infecção (pi), enquanto que os níveis de anticorpos IgG anti-VDN começaram a ser detectados mais tardiamente e atingiram um pico aos 14 dias pi. Além disso, a aplicação do ELISA em amostras de soro e de lágrima colhidas a partir de plantéis comerciais de galinhas de postura, para detecção de dois...
Keywords: Imunoglobulinas; Soro; Sorodiagnostico; Nucleoproteinas; Virus da doença de Newcastle; Newcastle disease virus